TRIB3 regulates FSHR expression in human granulosa cells under high levels of free fatty acids - Nan Wang; Chenchen Si; Lan Xia; Xian Wu; Sheng Zhao; Huihui Xu; Zhide Ding; Zhihong Niu (BMC, 2021)
Abstract Background Granulosa cells (GCs) in cumulus oophorus highly express follicle stimulating hormone receptor (FSHR), which is the most important mediator of both estradiol synthesis and oocyte maturation. Obese women have elevated free fatty acids (FFAs) levels in their follicular fluids and decreased FSHR expression in GCs, which is related to an altered protein kinase B/glycogen synthase kinase 3β (Akt/GSK3β) signaling pathway. Such FFA increases accompany 3-fold rises in pseudokinase 3 (TRIB3) expression and reduce the Akt phosphorylation status in both the human liver and in insulinoma cell lines. Therefore, in a high FFA environment, we determined if TRIB3 mediates regulation of FSHR via the Akt/GSK3β signaling pathway in human GCs. Methods GCs from women undergoing in vitro fertilization were collected and designated as high and low FFAs cohorts based on their follicular fluid FFA content. GCs with low FFA levels and a human granulosa-like tumor (KGN) cell line were exposed to palmitic acid (PA), which is a dominate FFA follicular fluid constituent. The effects were assessed of this substitution on the Akt/GSK3β signaling pathway activity as well as the expressions of TRIB3 and FSHR at both the gene and protein levels by qPCR, Western blot and immunofluorescence staining analyses. Meanwhile, the individual effects of TRIB3 knockdown in KGN cells and p-AKT inhibitors were compared to determine the mechanisms of FFA-induced FSHR downregulation. Results The average FSH dose consuming per oocyte (FSH dose/oocyte) was elevated and Top embryo quality ratio was decreased in women with high levels of FFAs in their follicular fluid. In these women, the GC TRIB3 and ATF4 protein expression levels were upregulated which was accompanied by FSHR downregulation. Such upregulation was confirmed based on corresponding increases in their gene expression levels. On the other hand, the levels of p-Akt decreased while p-GSK3β increased in the GCs. Moreover, TRIB3 knockdown reversed declines in FSHR expression and estradiol (E2) production in KGN cells treated with PA, which also resulted in increased p-Akt levels and declines in the p-GSK3β level. In contrast, treatment of TRIB3-knockdown cells with an inhibitor of p-Akt (Ser473) resulted in rises in the levels of both p-GSK3β as well as FSHR expression whereas E2 synthesis fell. Conclusions During exposure to a high FFA content, TRIB3 can reduce FSHR expression through stimulation of the Akt/GSK3β pathway in human GCs. This response may contribute to inducing oocyte maturation.